Where's the wisdom in service learning - Shumer, Robert, 1947- (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
The service-learning field is 50 years old in the United States. Much has been developed over that time in the fields of K-12 schooling, higher education, and community organizations. People who have been involved in the movement have worked individually and collaboratively to include servicelearning as an effective pedagogy and program in educational settings. They have created opportunities for students, teachers, faculty, and community members to learn about academic content and personal commitment to serving others for social change and community impact.In this book we hear from individuals who have been involved in the effort for more than 30 or 40 years about what they have learned from their experiences and what wisdom they can share with others who will be involved for the next several decades. Their experience, insight, and understanding will hopefully help younger people to improve and expand on the movement and place service-learning and community engagement as a regular part of American education.